The Rope Swing - Hunt,Roderick (Oxford university press, 1986)
"The Rope Swing" by Roderick Hunt, part of the Oxford Reading Tree series, features Biff, Chip, Kipper, and their friends as they discover a rope swing by a river. The children are excited to play, but they also face challenges and adventures along the way.
Keywords: Textbook